How have world shocks affected the business cycles of Africa's frontier economies? - Swanepoel, Debra-Lee (Research of GSB, 2018)
This paper builds on earlier work in business cycle theory, particularly in the growth cycle tradition of (Lucas, 1976), to analyse business cycles in Africa's Frontier Market Economies (FMEs), which include the following countries: Botswana, Ghana, Kenya, Mauritius, Mozambique, Nigeria, Tanzania, Uganda and Zambia. This paper extends the work of (Agenor, McDermott, & Prasad, 2000), (Rand & Tarp, 2002) and (R. L. Male, 2009) who have established a set of stylised facts for the fluctuations of business cycles in developing countries, to examine the impact of world shocks on the FMEs through the development of the stylised facts for these economies. This paper goes on to assess the suitability of the stylised facts that have been established for developing countries for Africa's FMEs. This thesis makes an important contribution to the literature, by focussing on Africa's FMEs which are also considered to be the anchors of growth and future development for the continent. In accordance with existing business cycle literature, this study examines the impact of endogenous and exogenous factors on the business cycles of the FMEs, to assess firstly how these factors impact the FMEs business cycles, and secondly whether there are similarities with other developing countries in terms of how these business cycles react to these impacts. The analysis is conducted through the examination of the volatility, persistence and cross-correlation between domestic output (gross domestic product) and a large group of macroeconomic variables (including consumption, fiscal variables, trade variables as well as monetary variables) to establish the stylised facts for the FMEs, which are then compared to the generalised stylised facts established for developing countries. The results indicate that only selected stylised facts for the analysis of business cycles of developing countries are valid for the FMEs, such as the volatility of output, public sector revenue and expenditure, and consumption. However, many aspects of the business cycles of these economies are significantly different to the stylised facts such as the lower than expected volatility of investment, as well as the volatility of exports which is double the expected value. The policy implications of the findings for Africa's FME's are also reflected upon.